The Influence Of Digital Marketing Strategy Search Engine Optimization, Word Of Mouth And Service Quality On Patients’ Decisions To Seek Treatment At Putri Hijau Hospital Medan - Lidia Henni Sembiring; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Jurnal Ners, 2025)
Health is a fundamental need for every individual in society. The rise in social status has led to increased demands for quality healthcare services. This situation encourages healthcare providers to continuously improve the quality of services provided. Patients' decisions regarding treatment are not only determined by personal factors but also influenced by external factors such as technological developments and changes in consumer behavior. One technique widely used to increase the visibility of healthcare services is Search Engine Optimization (SEO), which functions to increase website rankings in search engines. With the proper implementation of SEO, hospitals can be more easily found by potential patients seeking healthcare services. Furthermore, satisfied consumers are more likely to provide direct recommendations through word of mouth. This study aims to determine the influence of digital marketing strategies through SEO, word of mouth, and service quality on the decision to seek healthcare. The study used a descriptive analytical method with a cross- sectional design, meaning observations or measurements of variables were conducted at a specific point in time. The analysis results showed a significant influence of SEO on the decision to seek healthcare (p = 0.019), a significant influence of word of mouth on the decision to seek healthcare (p = 0.031), and a significant influence of service quality on the decision to seek healthcare (p = 0.006). Simultaneously, SEO, word of mouth, and service quality were proven to have a significant influence on patients' decisions to choose treatment (p < 0.005).